2010
DOI: 10.1111/j.1528-1167.2010.02772.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of visual field loss following exposure to vigabatrin therapy: A systematic review

Abstract: SUMMARYPurpose: Vigabatrin is an efficacious antiepileptic drug licensed as add-on therapy in refractory epilepsy and used in infantile spasms. Eight years after licensing, there emerged a strong and possibly causative association with bilateral visual field loss. We report a systematic review ascertaining the magnitude of risk of vigabatrin associated visual field loss (VAVFL) and any clinical predictors of risk. Methods: Electronic searches, including MEDLINE (1966), EMBASE (1974), and CINAHL (1982, were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 49 publications
(43 reference statements)
3
96
0
1
Order By: Relevance
“…The problem is that no reliable methods exist to detect whether or not visual field defects are developing ongoing vigabatrin therapy in infancy because they are not co-operative for perimetry assessment or measurements of the loss of retinal nerve fibre layer [32]. One recent systematic review showed that visual field defects occur in 40 % of adults and 34 % of older children receiving vigabatrin [68]. The earliest sustained onset of the vigabatrin-induced retinal defect studied by ERG is at 3 months [32].…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…The problem is that no reliable methods exist to detect whether or not visual field defects are developing ongoing vigabatrin therapy in infancy because they are not co-operative for perimetry assessment or measurements of the loss of retinal nerve fibre layer [32]. One recent systematic review showed that visual field defects occur in 40 % of adults and 34 % of older children receiving vigabatrin [68]. The earliest sustained onset of the vigabatrin-induced retinal defect studied by ERG is at 3 months [32].…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…There is an FDA black box warning for vigabatrin-induced, permanent, bilateral concentric visual field constriction in 30% or more of patients. [9][10][11][12][13] Peripheral visual loss can range from mild to severe tunnel vision to within 10°of visual fixation. In some cases, vigabatrin may damage the central retina, decreasing visual acuity.…”
Section: Vigabatrinmentioning
confidence: 99%
“…The estimated risk of developing a visual field defect is 8% per year in adults. 9,13 Because of this risk of permanent visual loss, vigabatrin is available only through a single national central pharmacy. A formal ophthalmologic assessment is required at baseline and every 3 months during therapy.…”
Section: Vigabatrinmentioning
confidence: 99%
“…Vigabatrin is very effective in West syndrome, particularly when caused by tuberous sclerosis. The drawback is the risk of vigabatrin associated visual loss (VAVL), which has been reported at levels of between 19 and 59 % in pediatric series with a median rate of 33 % [118]. Valproate and lamotrigine (LTG) are considered as a first-line treatment in LGS [33,119].…”
Section: Anti-epileptic Medications (Aeds)mentioning
confidence: 99%